High-Dose amoxicillin supported with clavulanic acid as empirical therapy in acute otitis media - Lahiry, Sandeep; Dalal, Krunal; Pawar, Ashwini; Kotak, Bhavesh (Asian Journal of Medical Sciences, 2021)
An increase in the daily dose of amoxicillin from 45 mg/kg to 90 mg/kg was introduced in late 2000 to respond to increasing presence of penicillin-resistant Streptococcus pneumoniae (PRSP) in Acute Otitis Media (AOM) and in other respiratory infections. The basis for this recommendation is a well understood mechanism of resistance among PRSP as well as established safety profile of amoxicillin with known tolerance to high doses. The addition of a standard dose of clavulanic acid provides protection against resistance present in other pathogens involved in AOM and other respiratory infections. A formulation of high dose of amoxicillin with standard dose of clavulanic acid has been developed to meet the increasing needs for efficacy against bacteria with growing antibiotic resistance. While, on the one hand, there is continued empirical use of standard/lower dose of amoxicillin (45 mg/kg/day) or a second- or third-generation cephalosporin in AOM, on the other hand, there is evidence of a rise in intractable cases (relapses or first-line therapy failures). In addition to this, an evolving disease bacteriology and regional variation in antibiotic susceptibility are determinants of clinical outcome in AOM. The current paper discusses the unmet areas and explains rationale behind guideline-directed empirical high-dose amoxicillin supported with clavulanic acid in AOM.